Quantitative weights and aggregation. - Calvo, T. (IEEE Transactions on fuzzy systems)
Based on the strong idempotency of aggregation operators, quantitative weights are incorporated into the fusion process. Our general method is compared with some previous specific cases. More details about weighted aggregation based on some penalty function is given. Further, weighted integral based aggregation linked to quantifier-based fuzzy measures is investigated, especially weighted OWA operators. Several examples are included.